Implementation of Clean Water and Sanitation Network Construction to Improve the Quality of Life Sea Tribe Communities - Martan, Viven; Yandi, Delpra; Sidabutar, Yuanita FD; Fauzan, Fauzan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The Riau Archipelago is a region consisting of islands surrounded by ocean. One of the inhabitants of the Riau Islands is the sea tribe or sampan tribe. The characteristic of this sea tribe is that they carry out their activities in canoes and move from one strait to another. Tiangwangkang is a small village in the south of Batam Island, to the right of the 1 Barelang Bridge. As an old village, Tiangwangkang has classic problems, namely the availability of clean water and wastewater management. To fulfill one of the SDG goals, namely ensuring the availability and sustainable management of clean water and sanitation for everyone, the Batam City Government has implemented the Construction of Clean Water/Drinking Water Facilities in Tiangwangkang Old Village which is connected to the ATB (now Moya) Main Pipe water source in Trans Barelang Road. This clean water network reaches Lance Island, Panjang Island, Akar Island, and Tanjung Undap via underwater pipes. To overcome the habit of people who defecate directly into the sea, the Batam City Government built communal IPAL sanitation facilities, where each house is connected to a network of wastewater pipes that flow to the Communal IPAL, then the wastewater is processed at the WWTP to produce clear and environmentally friendly water. With the development of infrastructure and the arrangement of Tiangwangkang Old Village, it is hoped that the quality of life of the community will improve, as well as become a comfortable tourist destination for tourists.